2021
DOI: 10.3390/ma14123325
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical and Electrical Properties of Epoxy Composites Modified by Functionalized Multiwalled Carbon Nanotubes

Abstract: This paper investigates the effect of multiwalled carbon nanotubes on the mechanical and electrical properties of epoxy resins and epoxy composites. The research concerns multiwalled carbon nanotubes obtained by catalytic chemical vapor deposition, subjected to purification processes and covalent functionalization by depositing functional groups on their surfaces. The study included the analysis of the change in DC resistivity, tensile strength, strain, and Young’s modulus with the addition of carbon nanotubes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 41 publications
(57 reference statements)
1
7
0
Order By: Relevance
“…Usually MWCNTs have a larger diameter (2.5–50 nm) than that of SWCNTs (0.5–1.0 nm), therefore MWCNTs reinforced epoxy composites should have a higher optimal CNT content φ opt than SWCNTs/epoxy composites (Figure 7 and Figure 8B). This was confirmed by many of previous works, [ 34,36,42,43,59,60,62,71–73 ] where the optimal CNT content φ opt for MWCNTs/epoxy composites is in the range of 0.25–2.0 wt% CNTs, which is much higher than the value of 0.05 wt% SWCNTs in this work. For example, Dehghan et al used MWCNTs with a diameter of 90–130 nm and length of 20–45 μm to reinforce epoxy and found that addition of 2 wt% MWCNTs into epoxy has the highest tensile strength.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Usually MWCNTs have a larger diameter (2.5–50 nm) than that of SWCNTs (0.5–1.0 nm), therefore MWCNTs reinforced epoxy composites should have a higher optimal CNT content φ opt than SWCNTs/epoxy composites (Figure 7 and Figure 8B). This was confirmed by many of previous works, [ 34,36,42,43,59,60,62,71–73 ] where the optimal CNT content φ opt for MWCNTs/epoxy composites is in the range of 0.25–2.0 wt% CNTs, which is much higher than the value of 0.05 wt% SWCNTs in this work. For example, Dehghan et al used MWCNTs with a diameter of 90–130 nm and length of 20–45 μm to reinforce epoxy and found that addition of 2 wt% MWCNTs into epoxy has the highest tensile strength.…”
Section: Resultssupporting
confidence: 90%
“…The above theoretical analyses indicate that the CNT content, radius and length all have the important influence on the tensile strength of composite, which can partly explain why the dependence of the fracture strength of composites on the CNT content is different for different works. [29,34,36,38,42,43,[59][60][61][62][63][71][72][73] CNTs used in these works were acid-treated, which actually are shortlength CNTs. However, the radius and practical length of CNTs in different works possibly are different.…”
Section: Modelmentioning
confidence: 99%
“…The development of the polymer's properties may arise trough the filling process with several nano-fillers such as fibers, semiconductors, organic, metals and inorganic constituent part besides carbon constructions. Epoxy resins are thermosetting polymers and they are the largest commonly used resins [2]. They are with low molecular weight organic liquids holding epoxide groups.…”
Section: Introductionmentioning
confidence: 99%
“…Polymer dielectrics are extensively utilized in electronic devices because of their easy processing, flexibility, and light weight [ 1 , 2 , 3 , 4 , 5 , 6 ]. However, the low thermal conductivity of polymer dielectrics cannot meet the rising demand of efficient heat dissipation due to continues miniaturization electronic devices with high speed and high power [ 5 , 7 , 8 , 9 ]. Incorporation of thermally conductive fillers into polymer matrix is regarding as an effective strategy to improve the thermal conductivity of materials [ 10 , 11 , 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%